2009
DOI: 10.1111/j.1468-2982.2009.01954.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases during and outside of migraine attacks without aura

Abstract: To test the hypothesis that permeability of the blood-brain barrier (BBB) is altered during migraine attack due to enhanced activation of matrix metalloproteinases (MMPs), we investigated MMP-3, MMP-9 and tissue inhibitor of metalloproteases (TIMP)-1 in the external jugular vein during and outside of migraine attacks in 21 patients with migraine without aura. In addition, we measured plasma levels of several other proteins including MMP-7, -8, -10 and TIMP-2. We used Rules-Based Medicine multi-analyte profilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 44 publications
0
25
1
1
Order By: Relevance
“…We sorted genes that were increased over 2-fold in the MCAO group compared with normal group, then screened for genes that were down-regulated more than 2-fold in the si-ASK1 group compared with the MCAO group. Several genes were selected, including matrix metallopeptidase 3 (MMP3) (Ashina et al, 2010), integrin alpha 8 (Itga8) (Cucullo et al, 2011;Osada et al, 2011), cadherin 1 (Cdh1) (Zechariah et al, 2013), gap junction protein beta 1 (Gjb3) (Song et al, 2007), Selectin (Sele) (Jin et al, 2010), intercellular adhesion molecule 1 (Icam1) (An and Xue, 2009), aquaporin 8 (Aqp8) (Richard et al, 2003), aquaporin 12 (Aqp12) (Calvanese et al, 2013) related with vascular permeability. Also, vascular endothelial growth factor A (Vegfa) (Gong et al, 2014;Poittevin et al, 2014), and vascular endothelial growth factor C (Vegfc) (Foster et al, 2008;Xu et al, 2013) which are related with vascular permeability were down-regulated in the si-ASK1 group compared with the MCAO group slightly.…”
Section: Resultsmentioning
confidence: 99%
“…We sorted genes that were increased over 2-fold in the MCAO group compared with normal group, then screened for genes that were down-regulated more than 2-fold in the si-ASK1 group compared with the MCAO group. Several genes were selected, including matrix metallopeptidase 3 (MMP3) (Ashina et al, 2010), integrin alpha 8 (Itga8) (Cucullo et al, 2011;Osada et al, 2011), cadherin 1 (Cdh1) (Zechariah et al, 2013), gap junction protein beta 1 (Gjb3) (Song et al, 2007), Selectin (Sele) (Jin et al, 2010), intercellular adhesion molecule 1 (Icam1) (An and Xue, 2009), aquaporin 8 (Aqp8) (Richard et al, 2003), aquaporin 12 (Aqp12) (Calvanese et al, 2013) related with vascular permeability. Also, vascular endothelial growth factor A (Vegfa) (Gong et al, 2014;Poittevin et al, 2014), and vascular endothelial growth factor C (Vegfc) (Foster et al, 2008;Xu et al, 2013) which are related with vascular permeability were down-regulated in the si-ASK1 group compared with the MCAO group slightly.…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature (19)(20)(21)(22), the 95% confidence interval for the difference in means of MMP-9 between the migraine group and the control group will be approximately 50 ± 30 ng/mL. It is expected that the confidence intervals for the inter-ictal and post-treatment differences in the treated group will be considerably narrower due to the elimination of patient-to-patient variation when analyzing our primary endpoint.…”
Section: Discussionmentioning
confidence: 97%
“…An alteration of MMP expression may lead to the breakdown of the BBB, demyelination, cytokine production and an inflammatory response, deposition of amyloid proteins, and tumor invasion and metastasis [14][15][16][17][18]. In migraine, post-headache levels of MMP-9 were significantly higher than controls [19][20][21][22]. MMP-9 potentiates chemokines for leukocyteendothelial cell interaction leading to an inflammation cascade at the brain vasculature.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we found that MA patients, but not MWA patients, had lower MMP-9 and higher TIMP-1 concentrations than healthy controls, thus suggesting that higher TIMP-1 levels could be associated with MMP-9 plasma reduction in MA patients, although we have not determined the mechanisms possibly involved in these differences. Another study showed that MMP-9 levels were not correlated with the frequency or duration of migraine attacks (Ashina et al, 2010). It is highly probable that some differences between studies may explain differences in MMP-9 levels.…”
Section: Discussionmentioning
confidence: 98%